PERBEDAAN METODE INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE DENGAN DEEP TISSUE MASSAGE DAN CONTRACT-RELAX STRETCHING DALAM MENINGKATAN LINGKUP GERAK SENDI SERVIKAL PADA MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS DI SMA NEGERI 1 SEMARAPURA - I Gede Donny Hendrawan; Nila Wahyuni; I Made Muliarta (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT Myofascial pain syndrome is a collection of sensory, motor, and autonomic symptoms that cause local and reffered pain, limited range of motion and weakness of the affected muscles. The limitations range of motion will be annoying than the daily activities. Interventions that can improve range of motion of cervikal are Integrated Neuromuscular Inhibition Technique, Deep Tissue Massage and Contract-Relax Stretching. The results show Group Neuromuscular Inhibition Technique with Wilcoxan Sign Rank Test obtained a mean difference of 13.7 with p = 0.000, while the test results Hypothesis Group Contract-Relax Stretching with Paired Sample T-test showed a mean difference of 12.1 with p = 0.000. Test the difference between Mann Whitney U-test showed no significant difference between the other group are obtained p = 0.420. These results indicate that there is no difference in increasing range of motion in both groups. Keywords: Range of motion of cervical, Upper Trapezius Muscle,Myofascial Pain Syndrome, Integrated Neuromuscular Inhibition Technique, Deep Tissue Massage, Contract-relax Stretching, Goniometer.